IS THERE A SERIOUS BREACH OF ASEAN CHARTER?: A CASE STUDY OF THE MYANMAR MILITARY COUP 2021 VIOLENCE AGAINST CIVILIANS - Limsiritong, Nattapat; SOOKHAKICH, Pattawee (Asian Crime and Society Review, 2023)
This article is written from the perspective of ASEAN Charter to explain that a serious breach of ASEAN Charter does not exist in the case of the Myanmar military coup violence against civilians in February 2021. To analyze why article 5(3) could not be activated in practice to address the Myanmar military coup 2021 violence against civilians as a serious breach of ASEAN Charter, there are three elements to analyze and found that (1) no definition of serious breach and non-compliance of charter, (2) the final responsible body to address an issue of serious breach and non-compliance of ASEAN Charter is ASEAN Summit under article 20(4) but in practice this article pass a duty to interpret its definition of serious breach of charter to ASEAN Secretariat which has a very limit power under article 51(2) and Rule 2(1) of Rules of procedure for the interpretation of the ASEAN Charter 2012, and (3) decision making mode for applying article 5(3) is belong to article 20(1) (consultation and consensus method) which is based on politic compromise way more than legal binding way. Hence to unlock article 5(3) for addressing an issue of serious breach of ASEAN Charter, ASEAN needs to revise the decision-making mode under article 20(1) of ASEAN Charter by applying the majority vote or negative consensus (reverse consensus) method for the ASEAN Summit instead of consultation and positive consensus.